Possible Crosstalk and Alterations in Gut Bacteriome and Virome in HIV-1 Infection and the Associated Comorbidities Related to Metabolic Disorder - Komal Shrivastav; Hesham Nasser; Terumasa Ikeda; Vijay Nema (Viruses)
Improved antiretroviral therapy (ART) has significantly increased the life expectancy of people living with HIV (PLWH). At the same time, other complications like metabolic syndrome (MetS) are coming up as new challenges to handle. This review aims to explore the emerging evidence of gut microbiome and virome alterations in human immunodeficiency virus-1 (HIV-1) infection and associated metabolic disorders, such as type-2 diabetes (T2DM) and cardiovascular disease (CVD), with a focus on their interplay, contribution to immune dysfunction, and potential as therapeutic targets. We conducted a comprehensive review of the current literature on gut bacteriome and virome changes in HIV-1-infected individuals and those with metabolic comorbidities emphasizing their complex interplay and potential as biomarkers or therapeutic targets. HIV-1 infection disrupts gut microbial homeostasis, promoting bacterial translocation, systemic inflammation, and metabolic dysregulation. Similarly, metabolic disorders are marked by reduced beneficial short-chain fatty acid-producing bacteria and an increase in pro-inflammatory taxa. Alterations in the gut virome, particularly involving bacteriophages, may exacerbate bacterial dysbiosis and immune dysfunction. Conversely, some viral populations have been associated with immune restoration post-ART. These findings point toward a dynamic and bidirectional relationship between the gut virome, bacteriome, and host immunity. Targeted interventions such as microbiome modulation and fecal virome transplantation (FVT) offer promising avenues for restoring gut homeostasis and improving long-term outcomes in PLWH.